Determinants of anaemia among adolescent girls in rural Varanasi, Uttar Pradesh - Yadav, Priyanka; Kumar, Alok; Kansal, Sangeeta (International Journal of Research in Medical Sciences, 2023)
Background: India is home to 253 million adolescents 10-19 years of age, among the largest cohorts globally. This age group comprises of individuals in a transient phase of life requiring nutrition, education, counselling and guidance to ensure their development into healthy adults. Adolescent girls are the most vulnerable group of population due to different reasons especially anaemia. Anaemia is a major public health problem worldwide. The aim of this study was to assess the prevalence of anaemia and associated factors among adolescent girls (10-19 years) in rural Varanasi, Uttar Pradesh. Methods: The present study was a community-based cross-sectional study conducted among 369 adolescent girls in rural Varanasi with a semi-structured and pretested questionnaire. Results: Study shows that the overall prevalence of anaemia among adolescent girls was 67.8% out of which 41.5% and 24.4% were mild and moderately anaemic respectively. Anaemia was significantly associated with age groups, birth order, menarche status, no. of days of menstruation, gap between two cycles, use of clothes/sanitary pads and no. of pads used during menstrual cycle. Conclusions: Study found some preliminary factors significantly associated with anaemia like low socio-economic status, higher birth order, and knowledge about menstrual hygiene practices. Anaemia continues to be a major public health problem in India despite multiple initiatives to address it among adolescent girls.